Value of Alarm Features in Dyspepsia for Predicting Significant Organic Lesions in Endoscopy (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: For a long older age and the presence of alarm features are regarded as indications for prompt endoscopy in patients with dyspepsia. We aimed to find out the value of alarm features in diagnosing serious organic upper gastrointestinal lesions in patients with dyspepsia.Material & methods: In this observational study clinical variables and endoscopic findings of consecutive patients with dyspepsia were recorded in a semi-structured questionnaire. Univariate and multivariate logistic regression was done stepwise to identify predictors for endoscopic findings. A simplified predictor model was built with the age and the presence of any predictor alarm feature to find out the diagnostic accuracy of this model for the significant endoscopic lesion.Results: Among 304 patients (M=134, F=170) one or more alarm features were present in 193 cases (63.5%). Significant organic lesions were found in 84(27.6%) cases. Age ≥ 45 years (OR 2.608), abdominal lump (OR 4.489) and family history of upper gastrointestinal cancer (OR 3.880) were found as independent predictors of major endoscopic findings. Using a simplified predictor model of age ≥ 45 years or the presence of any predictive alarm feature, sensitivity, specificity, positive predictive value, and negative predictive value were 32.4 %, 82.5 %, 79.8% and 36.4% respectively for a significant endoscopic lesion. For upper gastrointestinal cancers, these values were 6%, 100.0%, 100.0% and 47.3% respectively.Conclusion: The predictive value of the age and the presence of alarm features alone are not optimal for significant endoscopic findings in patients with dyspepsia. A newer and more accurate predictive model is a time demand for organic UGI lesions, especially for malignancies.J Bangladesh Coll Phys Surg 2023; 41: 132-140